DEVELOPING THE READINESS OF FUTURE MASTERS OF PSYCHOLOGISTS FOR PROFESSIONAL ACTIVITY AS A PSYCHOLOGICAL AND PEDAGOGICAL PROBLEM - Lariontseva, Anna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article is devoted to the analysis and determination of the relevance of the study of the problem of formation of readiness for professional activity of future master's degrees in psychology. The article substantiates the relevance of solving the problem, considers the theoretical issues of the foundations of the formation of the future psychologist's readiness for professional activity as a psychological-pedagogical problem, analyzes the views of modern domestic and foreign scientists regarding the professional training of future master's psychologists in institutions of higher technical education. Research methods. To achieve the goal in the work, it is planned to use a set of methods and techniques of scientific knowledge. Theoretical methods are highlighted, which involve the analysis of scientific literature on the topic of research and generalization of the obtained information, system analysis, generalization of theoretical and methodological approaches to the problem, development and justification of the theoretical model of the research subject. And also, the method of logical generalization - for theoretical substantiation of the significance of the tasks and clarification of the key concepts of the study. The results. The question of formation of professional qualities of the future specialist in the training process is revealed. Conclusions. The problem of professional training of master psychologists is quite acute. Expanding the field of activity of psychologists makes high demands on the personality of the specialist himself. The scale of the personality of graduates in institutions of higher technical education should correspond to the scale of professional tasks that modern life and society pose to master psychologists. And this, at the same time, requires correction of educational programs in institutions of higher education. In connection with the reform of education, the issues of innovative changes in the professional training of future specialists of various profiles are becoming the highest priority. The problem of transition from a knowledge paradigm to another methodological direction is being updated, which involves independent orientation of students in the world of information and forms professional competence in future specialists. Let us emphasize that attention is focused on the problem of professional training, and not only on education, which is one of the aspects of training future specialists